2010
DOI: 10.1016/j.ghir.2010.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Effects of combined hormone replacement therapy or its effective agents on the IGF-1 pathway in skeletal muscle

Abstract: Year-long postmenopausal HRT was found to affect the expression of the genes along the IGF-1 signaling cascade reflecting the higher muscle mass compared to the CO women. By using cell culture model we were, however, unable to confirm the possible differential role of E₂ and NETA. It appears that the synchronous presence of both effective agents of the HRT or the presence of yet unidentified microenvironmental factors providing proper paracrine signals naturally existing in the intact muscle tissue is critical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(25 citation statements)
references
References 59 publications
(63 reference statements)
0
25
0
Order By: Relevance
“…Other cross-sectional analyses have also shown lower circulating IGF-I concentrations in current HT users [21,24]. The results of several small trials (n b 100) of varying HT regimens are in agreement that oral conjugated oestrogen alone [25,26], or in combination with cyproterone acetate [27] decreases circulating IGF-I concentrations, but the addition of androgenic progestagens nullifies this response [26]; the results of these small trials show that oral conjugated oestrogen combined with norethisterone has no effect on circulating IGF-I concentrations [25][26][27][28]. Our results by HT type are consistent with the small trials; women currently taking oestrogen alone had the lowest plasma IGF-I concentrations, and although we were not able to further categorise the women taking oestrogen + progestagen by specific type of progestagen used, women taking these combined preparations had similar circulating IGF-I concentrations to women not currently using HT.…”
Section: Discussionmentioning
confidence: 78%
“…Other cross-sectional analyses have also shown lower circulating IGF-I concentrations in current HT users [21,24]. The results of several small trials (n b 100) of varying HT regimens are in agreement that oral conjugated oestrogen alone [25,26], or in combination with cyproterone acetate [27] decreases circulating IGF-I concentrations, but the addition of androgenic progestagens nullifies this response [26]; the results of these small trials show that oral conjugated oestrogen combined with norethisterone has no effect on circulating IGF-I concentrations [25][26][27][28]. Our results by HT type are consistent with the small trials; women currently taking oestrogen alone had the lowest plasma IGF-I concentrations, and although we were not able to further categorise the women taking oestrogen + progestagen by specific type of progestagen used, women taking these combined preparations had similar circulating IGF-I concentrations to women not currently using HT.…”
Section: Discussionmentioning
confidence: 78%
“…These findings point to an enhanced pro-anabolic muscle environment in both sedentary and exercising women exposed to HRT and pointing to a potential mechanism by which HRT manifests positive effects on muscle mass and function. Another recent study also demonstrated that yearlong exposure to HRT increases expression of genes associated with the insulin-like growth factor-1 (IGF-1) signalling cascade in post-menopausal females [21]. IGF-1 is a potent signal for muscle hypertrophy and satellite cell activation [22] and as such, these findings point to another likely mechanism by which HRT can positively influence skeletal muscle mass.…”
Section: Hrt and Muscle Function In Aging Femalesmentioning
confidence: 90%
“…The loss of satellite cells has been related to a decreased regenerative capacity of skeletal muscle (Collins et al 2005). Studies have identified a link between compromised muscular function, loss of muscle mass and the reduction of estrogen in postmenopausal women (Ahtiainen et al 2012, Pöllänen et al 2010, Ronkainen et al 2009). …”
Section: Discussionmentioning
confidence: 99%
“…When circulating estrogen levels are diminished, as seen in post-menopausal females, many of the beneficial effects of estrogen on these tissues are also lost. However a number of studies using human and animal models, have demonstrated that with estrogen replacement the protective and regenerative effects of estrogen on skeletal muscle, vascular, hepatic and neural tissues can be restored (Ahtiainen et al 2012, Bourque et al 2009, Dieli-Conwright et al 2009, Pike et al 2009, Pöllänen et al 2010, Ronkainen et al 2009, Suzuki et al 2009, Velders and Diel, 2013, Hsu et al 2015. Specifically in skeletal muscle, estrogen replacement soon after ovariectomy in rodents will also restore post-atrophy muscle regenerative capacity and diminish post-exercise muscle inflammation and damage indices (McClung et al 2006).…”
mentioning
confidence: 99%